Eros and Philia in Platonic philosophy - Montenegro, Maria Aparecida de Paiva (Revista Archai, 2025)
t is not easy to delimit the difference between the Platonic conceptions of Eros and Philia. In the dialogues mostly directed to the subject, like Lysis, Sympo-sium and Phaedrus, one may identify an overlap between both themes, in such a way that the analysis of the former leads to the study of the latter. In Lysis, whereas Philia is the focus of the debate between Socrates and Menexenus, the dialogue has as its background, and with a strong appeal, Hippothales’ love for Lysis. With regard to the Symposium, although Eros is the central theme of the dialogue, one may infer from Pausânias’ discourse, the distinction between the two kinds of Eros, in such a manner that the nobler is quite similar to what one may understand as being Philia. In Phaedrus, in its own turn, Philia appears as a mitigated Eros, so to speak. The present paper is an attempt aimimg at pointing out that in the above-mentioned dialogues Plato takes advantage of the approximation between Erosand Philia in order to found his proper conception of Philos sophia, according to which Eros plays a decisive role. In other words, a conception of philosophy according to which the Beautiful (Eros) may assimilate the Good (Philia). For this purpose, he proposes the following theses: (1) Desire is the cause for both Eros and Philia and as such presup-poses a relationship between lovers/friends; (2) Desire is characterized by a lack (either present or future); (3) What is really lacking is something that has been lost; (4). Desire is a move of the soul towards the recovery of something lost, that is, the awesome contemplation of Beauty; Philosophy is the route, guided by Eros, of recovering Beauty.